2018
DOI: 10.1371/journal.pone.0205884
|View full text |Cite
|
Sign up to set email alerts
|

System dynamics modelling approach to explore the effect of dog demography on rabies vaccination coverage in Africa

Abstract: BackgroundDogs are important reservoirs of rabies, a zoonotic viral encephalitis that kills thousands of people in Asia and Africa annually. Mass dog vaccination is recommended for the prevention of rabies in both humans and dogs. Mass vaccinations should be conducted annually but more frequent campaigns may be required in areas with high dog turnover rates. Consequently, a good understanding of dog demography is essential for the control of the disease. The aim of this study was to explore the effect of dog d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 49 publications
0
19
0
3
Order By: Relevance
“…4 ). Using Vensim™ with a stock and flow approach, a population dynamic model was developed as follows: the population variable was considered as stock, and the birth and death variables as flows, and birth, death rates and, carrying capacity were considered as auxiliary variables 14 , 69 . Weather, food resources and rehoming/abandonment were not used in the model and no immigration and emigration was assumed in the population.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 ). Using Vensim™ with a stock and flow approach, a population dynamic model was developed as follows: the population variable was considered as stock, and the birth and death variables as flows, and birth, death rates and, carrying capacity were considered as auxiliary variables 14 , 69 . Weather, food resources and rehoming/abandonment were not used in the model and no immigration and emigration was assumed in the population.…”
Section: Methodsmentioning
confidence: 99%
“…When comparing different interventions, fertility control may most greatly reduce free-roaming dog population and improve animal welfare 11 , 12 . The efficacy and impact assessment of different FRD populations management plans should be considered in terms of reducing dog population density, improving public health and animal welfare, and performance of DPM facilities 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“…However, different levels of vaccination coverages, as well as vaccination strategies, are probably required to control rabies in different settings successfully. For instance, according to modeling studies conducted for dog populations in Africa, vaccination with 70% coverage annually is adequate to sustain herd immunity above a critical threshold [ 16 , 52 ]. However, based on our modeling results, vaccination coverage of 70% in Hatyai might still be insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in a growing or high turnover population, the outbreaks will likely be larger and longer (only 4% of all outbreaks lasted longer than a year in this study) and the vaccination strategies might perform differently–overall vaccination coverage might not be achieved with targeted strategies, or targeting explorer and roamer dogs could be even more critical to stop rabies spread. Some studies have modelled vaccination campaigns in high turnover dog populations and have found that annual vaccination with 70% coverage is sufficient to maintain herd immunity above a critical level [42, 43]. However, these studies were performed on rabies endemic populations.…”
Section: Discussionmentioning
confidence: 99%